Ideologi Penerjemahan Teks Teknis - Santi Oktaviani (Swara Patra, 2019)
This paper discusses the translation ideology including foreignization and domestication accompanied by translation methods in accordance with the translation ideology. Foreignization is oriented towards the source language by presenting source language culture into translated texts as a means of communication so the readers of translations understand the culture of the source language that is different from the culture of the target language. The translation methods that are in accordance with foreignization are word-by-word translation, literal translation, faithful translation, and semantic translation. Domestication is oriented towards the target language by transferring the source language cultural values to the target language so that it is more easily understood by the readers of the translation. Translation methods that are in accordance with domestication are adaptation, free translation, idiomatic translation, and communicative translation. Library studies are used in this paper by reviewing theories, references, and other scientific literature including the results of previous studies. It is found that in the translation of technical texts, two translation ideologies and methods of translation could appear to be varied influenced by various factors, including the purpose of translation and translation text readers (target readers).